The Silent Risks of Sleepless Nights: Can short sleep duration be considered a significant risk factor for hypertension? - A literature review - Chudzikowski, Marcel; Dudek, Patryk; Łuczak, Klaudia; Pawlik, Agnieszka; Pięta, Justyna; Prokopiuk, Agata; Prus, Joanna; Sitarek, Hanna; Tabeau, Adrianna; Ulicka, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose Hypertension is one of the most common diseases worldwide affecting more than 30% of the global adult population. It can lead to serious complications. Making it a major concern for modern medicine. While traditional risk factors such as obesity, diet and lifestyle choices are well known, recent evidence suggests that short sleep duration may also play a significant role in the development of hypertension. The aim of this study is to summarise information on the impact of short sleep duration on the incidence and pathophysiology of hypertension. Methods A systematic review of scientific articles published between 2015 and 2024 was conducted using PubMed. Articles were searched using the following terms: hypertension, high blood pressure, short sleep duration, sleep deficiency . Brief Description Of The State Of Knowledge Current literature suggests that sleep deprivation influences blood pressure regulation through multiple pathways, including autonomic nervous system dysfunction, increased inflammation, oxidative stress, and metabolic disturbances. Observational studies indicate a higher incidence of hypertension among individuals sleeping less than six hours per night, with variations based on age and sex. Meta-analyses confirm the relationship, where short sleep durations correlate with increased hypertension risk. Summary Short sleep duration is a modifiable yet often overlooked risk factor for hypertension. Given the high prevalence of sleep deficiency in modern society, integrating sleep hygiene recommendations into hypertension prevention strategies may be beneficial. Further research utilizing objective sleep measurements is essential to establish causality and develop targeted interventions.